Police Order 2002: A Critique - Umbreen Javaid; Muhammad Ramzan (Journal of Political Studies, 2013)
Pakistan inherited police law from British and there was a need to change it according the requirements of the new state. A number of committees and commissions were formed to reform the police but their recommendations could not be implemented. Military government of Pervez Musharraf took it on itself to bring reform in policing and promulgated Police Order 2002 replacing the colonial Police Act 1861 with an aim to make police a truly professional, service oriented, operationally autonomous and democratically accountable organization. The new law introduced some new institutions of public oversight and accountability of police at district, provincial and national levels. These include Public Safety Commissions and Police Complaint Authorities. Members of these institutions are to be taken from law makers and civil society. Through these institutions a system of accountability of police by independent bodies was introduced on the one hand and the police was insulated from political interference on the other. Some objections were raised on the Police Order by provinces and civil society members. Under the pressure from the provinces, some basic amendments were made in the law in 2004 which diluted the authority of oversight bodies and increased the role of executive bureaucracy and politicians in key police appointments.